P255 Once-daily Tiotropium Respimat® Add-on To At Least Ics Maintenance Therapy Reduces Exacerbation Risk In Patients With Uncontrolled Symptomatic Asthma. (10th November 2014) - Halpin, DMG; Paggiaro, P; Bleecker, E; Engel, M; Moroni-Zentgraf, P; Schmidt, H; Kerstjens, HAM
Abstract : Background: A reduction in asthma exacerbation risk may provide improvements in clinical burden, patient experience and healthcare costs. In Phase III trials, once-daily tiotropium (delivered via the Respimat ® SoftMist™ inhaler) added on to at least inhaled corticosteroids (ICS) improved lung function in patients with symptomatic asthma. We investigated exacerbation risk in each trial. Methods: Five Phase III, double-blind, placebo-controlled, parallel-group trials in patients with symptomatic asthma. Patients received tiotropium Respimat ® 5 µg or placebo as add-on to at least ICS maintenance therapy (Table). Pre-planned co-primary or secondary end points were time to first severe exacerbation and time to any asthma worsening. Results: Mean baseline% of predicted forced expiratory volume in 1 second, seven-question Asthma Control Questionnaire score and ICS dose (µg) were: 56.0 ± 13.1, 2.6 ± 0.7, 1198 ± 539 (PrimoTinA-asthma ® ); 75.1 ± 11.5, 2.2 ± 0.5, 660 ± 213 (MezzoTinA-asthma ® ); 77.7 ± 11.9, 2.1 ± 0.4, 381 ± 78 (GraziaTinA-asthma ® ). Tiotropium Respimat ® 5 µg reduced severe asthma exacerbation risk by at least 21% in all three severity cohorts (Table) and asthma worsening risk versus placebo in all trials, with a statistically significant reduction in the PrimoTinA-asthma ® trial. Conclusion: Once-daily tiotropium Respimat ® 5 µg add-on to at least ICS maintenance therapy consistently reduced exacerbations across asthma severities and so may be a beneficial add-on option to reduce current and future exacerbation risk.